INDIVIDUAL SECTOR OF AGRICULTURE IN MOLDOVA: A PATH TO RURAL DEVELOPMENT? - Liliana CIMPOIES; Elena SEMIONOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The individual farms are the backbone of rural areas and account more than 80% of all farms. Family farms are quite diverse: from subsistence and semi-subsistence to fully market-oriented farms, often using technologies advances. Presently, the agricultural sector of Moldova is divided into two categories: a large number of small individual farms and some large corporate farms. The investigation is analysing the level of development of individual farms in Moldova and its possible contribution to the development of rural areas. The study is based on individual farms survey. The data was collected as part of the institutional research project 15.817.05.31А “Sustainable Rural Development in the Republic of Moldova in the Context of European Integration”. It includes data analysis of 938 individual farms from 9 different districts. The survey includes different parts related to: the social-demographic characteristics, infrastructure and financial information. The obtained results shows changes in the social demographic aspects, mostly generated by the migration process and the “modest” incomes characteristic for rural areas. The individual farms surveyed present the average technical efficiency which is mostly influenced by the level of income and the small size of agricultural area, while the level of expenses has little influence.